Novel, cost‐effective, Cu‐doped calcium silicate nanoparticles for bone fracture intervention: Inherent bioactivity and in vivo performance. Issue 2 (15th April 2018) - Mabrouk, Mostafa; ElShebiney, Shaimaa A.; Kenawy, Sayed H.; El‐Bassyouni, Gehan T.; Hamzawy, Esmat MA
Abstract: Copper (Cu)‐doped calcium silicate nanoparticles were synthesized by a wet precipitation method as economical bone fracture filler. The aim was to improve the overall physicochemical properties, bioactivity, and biological performance of the bone fracture filler prepared herein. The synthesized nanoparticles were evaluated using X‐ray diffraction (XRD), Fourier transform infrared spectroscopy (FT‐IR), and transmission electron microscopy (TEM). The bioactivity of the prepared nanoparticles was investigated after immersion in simulated body fluid (SBF) by means of inductively coupled plasma (ICP), SEM coupled with energy dispersive X‐rays (EDX), and FTIR. The size and bioactivity of the prepared nanoparticles after 15 days of immersion in SBF was dependent on the Cu concentrations. The fracture healing ability of the fabricated nanoparticles on adult aged male Wistar rats was enhanced by the presence of copper. All the obtained results are of high relevance for fabricating improved Cu‐doped calcium silicate nanoparticles (∼50 nm) as low cost bone fracture filler. In addition, the in vivo study presented complete healing of the tibiae bone with normal architecture of bone tissue specifically calcium silicate nanoparticles doped with 3% and 5% Cu. Hence, the presence of copper is a promising tactic for improving the biological properties of calcium silicate. Therefore, the designed nanoparticles have huge potential for the treatment of bone fractures. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 107B: 388–399, 2019.